Analysis of Nucleoside Phosphorylase Polymorphism in Capra Hircus - Sekaran, M.; Selvaraj, O. S.; Tan, S. G.; Mukherjee, T. K.; Barker, J. S. F. (1989)
Nucleoside phosphorylase (NP) (E.C. 2.4.2.1) catalyses the phosphorolytic cleavage of certain purine nucleotides. We have analysed NP from nred cells of goats (capra hircus) on cellulose acetate gels and observed bands that are eIther intensely stained or weakly stained. However we did not observe any difference in band migration. This paper describes the use of a simple srectrophotometric assay as a means of typing blood samples collected from various regions of South East Asia. Good correlation has been obtained between intensities of staining of bands on electrophoretic gels and enzyme activities as measured spectrophotometrically.The bands that were intensely stained showed high enzyme activities whereas those that were weakly stained showed low enzyme activities when measured spectrophotometrically. Family studies support the hypothesis that the variation noticed is due to two allomorphIc gene one specifying high activity and the other low activity.